Новые точные решения уравнения Дирака; Известия вузов. Физика; Т. 23, № 4 - Багров В. Г. Владислав Гаврилович; Гитман Д. М. Дмитрий Максимович; Задорожный В. Н. Валерий Николаевич; Лавров П. М. Петр Михайлович; Шаповалов В. Н. Владимир Николаевич (1980, 1980)
Заглавие с экрана